2022
DOI: 10.1039/d2cc01528e
|View full text |Cite
|
Sign up to set email alerts
|

Triazine-pyridine chemistry for protein labelling on tyrosine

Abstract: Herein, we discover the new reactivity of 1,3,5-triazine moiety reacting with the phenol group and report the development of the biocompatible and catalyst-free triazine-pyridine chemistry (TPC) for tyrosine labelling under...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…We characterized peptides 5 and e5 by HRMS and NMR spectroscopy (Figures S2 and S3). The results of comparing the NMR spectra of e5 and 5 indicated that only the phenolic hydroxyl group of the tyrosine side chain participated in the reaction, which was consistent with results from our previous research …”
supporting
confidence: 91%
See 1 more Smart Citation
“…We characterized peptides 5 and e5 by HRMS and NMR spectroscopy (Figures S2 and S3). The results of comparing the NMR spectra of e5 and 5 indicated that only the phenolic hydroxyl group of the tyrosine side chain participated in the reaction, which was consistent with results from our previous research …”
supporting
confidence: 91%
“…The results of comparing the NMR spectra of e5 and 5 indicated that only the phenolic hydroxyl group of the tyrosine side chain participated in the reaction, which was consistent with results from our previous research. 21 To assess whether this stapling approach could improve peptide stability in plasma, we applied this strategy to αconotoxin IM1 (a toxin peptide from cone snail) and RGD peptide (an Arg-Gly-Asp peptide). Peptides 9 and 10 were obtained by introducing tyrosine at both ends of these two peptides (Table S1).…”
mentioning
confidence: 99%
“…It mainly reacts with the side-chain amino groups of collagens to form strong covalent bonds, thus enhancing hydrothermal stability of leather [22]. Compared with other organic tanning agents (e.g., aldehydes and syntan), triazine derivatives can effectively mitigate the health risks due to their biocompatibility [23,24]. Meanwhile, the released H + in tanning process (Additional file 1: Fig.…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 99%
“…[10][11][12] Key reactions of bioorthogonal chemistry include Staudinger ligation or native chemical ligation, strain-promoted [3 + 2] azide-alkyne and alkyne-nitrone cycloaddition (SPAAC and SPANC) reaction, dienophile and tetrazine inverse electrondemand Diels-Alder (IEDDA) ligation, oxime, and hydrazone ligations along with photoinducible bioorthogonal reactions. 4,13 As such, the IEDDA ligation techniques are quite promising and have been applied in various fields. [14][15][16][17] A robust synthesis of this IEDDA partner was reported by the Fox group in 2008 utilizing a one-step reaction around flow photo isomerization.…”
Section: Introductionmentioning
confidence: 99%